O „podkarpackich” wierszach do braci (w stronę antropologii listu poetyckiego; rekonesans) - Kuczera-Chachulska Bernadetta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The sketch deals w ith the problems of the poetic letter. During the exemplification of the issue, poems by Julian Przyboś, Cyprian Norwid and Ignacy Krasicki are used. It turns out that important issues can be seen from the perspective of selected, but also deep anthropological problems, arising from the interpretative process. The tools for understanding them are provided by thinkers of post-Husserlian phenomenology, in this case Dietrich von Hildebrand.
On ‘Podkarpackie’ Poems to Brothers (Towards Anthropology of a Poetic Letter; Reconnaissance)
Szkic ten jest zmienioną, przepracowaną i rozszerzoną wersją referatu wygłoszonego na konferencji „Podkarpacie literackie na przestrzeni wieków” Rzeszów – Przemyśl, 24–26 kwietnia 2018 r. Ani wersja pierwotna, ani obecna nie były nigdzie drukowane.
Keywords: Poetic letter; Przyboś; Norwid; Krasicki; brother; person; emotions; list poetycki; Podkarpacie; brat; osoba; uczucia